(untitled) (Communications in Computational Physics, 2020)
It is found that imaginary time propagation method can effectively deliver a convergent result in solving Kohn–Sham equation, but a sufficient long simulation is needed to reach an accurate enough result, while the self-consistent field iteration method for Kohn–Sham equation can be more efficient when it works, but it sometimes suffers from divergence. In this work, we take advantage of the convergence of imaginary time propagation method by generating a quality initial guess to improve the behavior of self-consistent field iteration. A number of numerical experiments successfully show that i). for those self-consistent field iterations which are sensitive to the initial guess, the results obtained from imaginary time propagation method make the iterations converge, and ii). generally, the convergence of self-consistent field iteration can be accelerated by imaginary time propagation method. It is shown that all-electron models can be resolved well with the proposed method.